7-6k+3k-5=

Simple and best practice solution for 7-6k+3k-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-6k+3k-5= equation:


Simplifying
7 + -6k + 3k + -5 = 0

Reorder the terms:
7 + -5 + -6k + 3k = 0

Combine like terms: 7 + -5 = 2
2 + -6k + 3k = 0

Combine like terms: -6k + 3k = -3k
2 + -3k = 0

Solving
2 + -3k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -3k = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -3k = 0 + -2
-3k = 0 + -2

Combine like terms: 0 + -2 = -2
-3k = -2

Divide each side by '-3'.
k = 0.6666666667

Simplifying
k = 0.6666666667

See similar equations:

| 7x+6+(x+2)=4x-2*3 | | -8-5y=15-d | | 24+3+12x=10+4x-3x | | 10+971(1673%10)= | | x^3-6x^2-3x-16=0 | | x^3-6x^2-3x-10=0 | | 3.2z=14 | | x^3-6x^2+3x-16=0 | | 8y+8-3y+6=2y+14 | | 44x=32x | | 3=7b+13-2b | | 6=-2n+s | | 4x^2+6x-2=x^2-2x+1 | | 4x^2+6x-2=x^2-2x+2 | | kx^2+12x+12=0 | | 0=8x-(3-z) | | -y-8+8y=-9+5y+1 | | 2x-6-4x-16=4x-1*3 | | 6a-11=19 | | 3x^2-kx+30=0 | | 6*(-1)=7-4y | | 2*x+4=6 | | -8(x-4)=4(x-12) | | 1+5x-2x=-2+3x+15x | | (.02)35+.09(x)=.04(35+x) | | -9+9x-5x-x=6+x-x | | 4(-8r+5)=-32r-26 | | 27=5r+2 | | 75-3x=10x-23 | | 4-(2x)=12 | | 20x=15(x+5) | | x+12=28x+3 |

Equations solver categories